2019
DOI: 10.1212/wnl.0000000000007717
|View full text |Cite
|
Sign up to set email alerts
|

Limbic neurochemical changes in patients with functional motor symptoms

Abstract: ObjectiveTo assess by magnetic resonance spectroscopy (MRS) the N-acetylaspartate, myo-inositol, choline, sum of glutamate and glutamine (Glx), and creatine (Cr) content in the anterior cingulate cortex (ACC)/medial prefrontal cortex (mPFC) and in the occipital cortex (OCC) (control region) in patients with functional motor symptoms (FMS) and healthy controls, and to determine whether neurochemical limbic changes as estimated by MRS correlate with FMS-related motor symptom severity, alexithymia, anxiety, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
3
17
2
Order By: Relevance
“…A major limitation of the study concerns the lack of information regarding the role played by glutamate in the production of SSD in our patients with PD. Although a recent study has indicated the presence of increased Glx/Cr in the mPFC of patients affected by functional motor symptoms, 71 we did not find differences in Glx levels among our cohorts. Methodological limitations impact somehow the heuristic value of the finding, as the Glx signal is composed of a mix of glutamate and glutamine, and 1 H‐MRS is unable to discriminate the distinct contribution of the 2 metabolites.…”
Section: Discussioncontrasting
confidence: 99%
“…A major limitation of the study concerns the lack of information regarding the role played by glutamate in the production of SSD in our patients with PD. Although a recent study has indicated the presence of increased Glx/Cr in the mPFC of patients affected by functional motor symptoms, 71 we did not find differences in Glx levels among our cohorts. Methodological limitations impact somehow the heuristic value of the finding, as the Glx signal is composed of a mix of glutamate and glutamine, and 1 H‐MRS is unable to discriminate the distinct contribution of the 2 metabolites.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are also in accordance with functional neuroimaging studies that showed increased activity of limbic and paralimbic regions (Aybek et al 2015;Espay et al 2018;Demartini et al 2019), and alterations in the amygdala, orbitofrontal cortex, and the insula, associated with the abnormal emotional processing in FMD (Voon et al 2010;Pick et al 2019). These regions contribute to the gustatory central process, in terms of quality of the perception, intensity, reward value, and hedonicity rating.…”
Section: Discussionsupporting
confidence: 92%
“…Growing evidence suggests that abnormalities in glutamatergic neurotransmission, via the N-methyl-D-aspartate receptor (NMDA-R), have a key role in the pathophysiology of several neuropsychiatric conditions, such as schizophrenia, mood disorders, and Alzheimer's disease [2][3][4] . Recently, a possible role of glutamate + glutamine (Glx) has been suggested in the pathophysiology of FMDs (also called conversion disorders), a neuropsychiatric condition characterized by the presence of motor symptoms that cannot be explained by typical neurological diseases or other medical conditions 5 . Although they are highly prevalent and have a considerable impact on national health systems, the pathophysiology of FMD remains unclear.…”
mentioning
confidence: 99%
“…Functional neuroimaging studies have underlined abnormalities in FMD at the level of brain network activity, connectivity, and specific anatomic areas of altered metabolic demand during tasks (mainly the limbic system) 7 . With respect to Glx, Demartini et al 5 recently showed, through a brain magnetic resonance spectroscopy (MRS) technique, that patients with FMD presented significantly higher levels of Glx in the limbic system than healthy controls. The authors hypothesized that abnormal increase in Glx in the limbic system might have a central pathophysiological role in FMD onset and maintenance, possibly by altering limbic–motor interactions.…”
mentioning
confidence: 99%